Fatigue and lack of vigor’s as a frequent work stress among financial workers in Indonesia - Rokhim, Rofikoh; Takwin, Bagus; Basrowi, Ray Wagiu; Soemarko, Dewi Soemaryani; Rahadian, Andre; Ekowati, Maria; Samah, Kristin; Moeloek, Nila Djuwita F. (Frontiers in Public Health, 2025)
This study examines work stress in the Indonesian financial sector by analyzing the prevalence of negative vigor, work fatigue, and the imbalance between work and personal life. Using a cross-sectional survey design, data were collected from employees across various financial institutions. Bivariate analysis revealed significant associations between work stress and key risk factors, with over 20% of employees reporting loss of work spirit (negative vigor) and fatigue. The results showed that younger employees (under 40 years old) are 2.5 times more likely to experience fatigue compared to older workers. Additionally, staff-level employees exhibited higher incidences of fatigue and vigor loss. The analysis also found a significant link between poor work-life balance and elevated stress levels, highlighting the lack of boundaries between personal and professional life as a key contributor to stress. These findings mirror global trends in the financial sector, where vigor loss and fatigue are significant factors in job dissatisfaction and productivity loss. The study underscores the need for targeted mental health interventions and organizational policies to address work stress and improve employee well-being.